The amendment of the U.S. stock act and the prices of stocks most held by congress. Issue 4 (2nd October 2018) - Blau, Benjamin M.; Whitby, Ryan J.; Wilson, Josh
Abstract : This paper examines the returns of stocks most frequently held by members of the US Congress surrounding the amendment to the "Stop Trading on Congressional Knowledge" (STOCK) Act, which relaxed some of the restrictions that kept congressional staffers from trading on non-public information. Using a series of standard event study techniques, we find evidence that the stocks held most by members of Congress outperformed the market during the period immediately surrounding the amendment's passage. Our results are robust to different treatment samples, various methods of calculating abnormal returns, and a number of different placebo tests. In addition, our multivariate tests show that the positive CARs surrounding the amendment are driven by the number of congressmen holding the stock and the amount invested by members of Congress in a particular stock.